2018
DOI: 10.1016/j.jaad.2018.02.040
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 17, inflammation, and cardiovascular risk in patients with psoriasis

Abstract: In addition to being recognized as a chronic inflammatory disease that manifests in the skin, psoriasis is increasingly understood to be a systemic disease that causes immune dysregulation throughout the body. The systemic nature of psoriasis is evidenced by the higher burden of comorbidities and shorter life expectancies of patients with psoriasis, particularly those with early-onset and severe disease. Notably, psoriasis is associated with an increased risk for cardiovascular disease, which is the most commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
71
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 96 publications
6
71
0
4
Order By: Relevance
“…For instance, patients with psoriasis share certain genetic traits with those who have diabetes and dyslipidemia . There is also an overlap in the inflammatory pathophysiology between psoriasis and CV diseases, as evidenced by involvement of various inflammatory cells and mediators, such as C‐reactive protein, tumour necrosis factor‐α, Th17 and interleukin‐17A, in both diseases . The increased prevalence of hyperhomocysteinaemia in patients with psoriasis found in our meta‐analysis further contributes to an understanding of the multifactorial nature of the relationship between the skin disorder and CV diseases.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…For instance, patients with psoriasis share certain genetic traits with those who have diabetes and dyslipidemia . There is also an overlap in the inflammatory pathophysiology between psoriasis and CV diseases, as evidenced by involvement of various inflammatory cells and mediators, such as C‐reactive protein, tumour necrosis factor‐α, Th17 and interleukin‐17A, in both diseases . The increased prevalence of hyperhomocysteinaemia in patients with psoriasis found in our meta‐analysis further contributes to an understanding of the multifactorial nature of the relationship between the skin disorder and CV diseases.…”
Section: Discussionmentioning
confidence: 57%
“…Psoriasis is a T helper cell (Th)1‐ and Th17‐mediated chronic inflammatory disease with a worldwide prevalence of around 2% . A growing body of evidence from clinical and epidemiological research has revealed an association between psoriasis and cardiovascular (CV) diseases, such as stroke, coronary heart diseases and peripheral vascular diseases .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the existence of shared cytokine pathways could play a role in the increased incidence of ischaemic heart disease and cerebrovascular disease in psoriasis patients with depression. 42 Th1 and Th17 cells and their associated cytokines have been demonstrated to be involved in the pathophysiology of psoriasis, 43,44 depression [45][46][47] and atherosclerosis. [48][49][50] In addition, other clinical and lifestyle-related factors may contribute to the increased vascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…Psoriatic and atherosclerotic plaques have similar underlying immunological mechanisms, in which T helper (Th)1 and Th17 cells release TNF‐α, IFN‐γ, IL‐17 and IL‐22, which contribute to keratinocyte activation and hyperproliferation, as well as to atherosclerotic plaque growth, instability and rupture . Obesity is associated with a low‐grade chronic systemic inflammation because it drives metabolic and immunological pathways including Th17 cell differentiation, which play a pivotal role in psoriasis pathogenesis.…”
mentioning
confidence: 99%